(untitled) (Hekima Review, 2010)
In the opening chapters of his book, Chishala discusses the measure of democracy which is often appraised in terms of elections. While discussing the role of media during the 2008 Presidential Election in Zambia, Chishala argues that good governance, the rule of law, promotion of human rights, press freedom, separation of powers in the organs of government, are crucial tenets that merit democracy but such issues seldom receive consideration in the measure of democracy. Chishala expresses that the practice of good democracy is shaped by good media coverage, which he contrasts with the developed world where the media has an impact on how governments are run. The author notes that due to inaccessibility to media in many parts of Africa, let alone illiteracy and poverty, the media often faces blackouts. Nevertheless, the author also admits that radio broadcasting, especially to rural areas, has been successful because of the diversity of programs designed to address various audiences including those who are illiterate.